TENDENCY OF CYBERBULLYING BEHAVIOR AMONG HIGH SCHOOL STUDENTS IN MOJOKERTO - Reza Nanda Ramadhan; Ansyah, Eko Hardi (PT. Antis International Publisher, 2025)
Objective: This research was aimed at examining how big is the tendency for cyberbullying behavior among high school students in Mojokerto. Method: The type of this research is quantitative experimentation with research techniques using experiments. There were 65 respondents in this study aged 15-17 years. This study used a Likert scale to obtain research data. Results: The results attained in this research demonstrated a tendency for cyberbullying behavior in vocational school students at the age of 17 for boys, this was proven by the high score on these criteria. Novelty: The function of overcoming the problem of cyberbullying is to provide socialization to the public regarding the problem of hackers/cyberbullying, one of the negative impacts of the rapid development of technology and social media.